2020
DOI: 10.1177/1751143720928895
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the practices and capabilities in the management of respiratory failure in South East England

Abstract: Introduction The variability of acute respiratory distress syndrome management may affect the referral practice to severe respiratory failure centres. We described the management of acute respiratory distress syndrome in our catchment area. Methods An electronic survey was administered to 42 intensive care units in South-East England. Results Response rate was 71.4%. High-flow nasal oxygen and non-invasive ventilation were used ‘often’ in moderate-acute respiratory distress syndrome by 46.7% and 60%. During in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A survey of critical care specialists found that only 8% would consider HFOV as rescue while 26% would likely never utilize it ( Alhurani et al, 2016 ). Additional studies have shown HFOV use to be rare in the current era, with one reporting 4.3% of rescue cases ( Duan et al, 2017 ), another reporting 1.7% of ventilator epochs ( Jabaley et al, 2018 ), and only 10% of ICUs in the UK reporting any HFOV use ( Jha et al, 2021 ). In 2021, the use of HFOV was reported in a single center study of 48 subjects with a OI 36 and a mortality rate of 92% ( Thind et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of critical care specialists found that only 8% would consider HFOV as rescue while 26% would likely never utilize it ( Alhurani et al, 2016 ). Additional studies have shown HFOV use to be rare in the current era, with one reporting 4.3% of rescue cases ( Duan et al, 2017 ), another reporting 1.7% of ventilator epochs ( Jabaley et al, 2018 ), and only 10% of ICUs in the UK reporting any HFOV use ( Jha et al, 2021 ). In 2021, the use of HFOV was reported in a single center study of 48 subjects with a OI 36 and a mortality rate of 92% ( Thind et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%